OBSERVASI SELFIE PARA PEKERJA FAST MOVING CUNSUMER GOODS SAAT PANDEMI COVID-19 - Sarwo Nugroho (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
Taking selfies for documentation reasons mentioned by Rettberg (2014) and Chae (2017). Likewise, this study reports documentation and archiving, which is part of communicating self-motives. Additionally, this research draws attention to general digital effects such as special event filters and seasonal filters used with selfies to signal specific locations or events. In their research, Senft and Baym (2015) noted that selfies can be used as an empowering tool to overcome political problems. This research shows how selfies are used as an empowering tool to educate Saudi women, particularly about their legal rights. The use of selfies as an educational tool in the context of public problems has not been reported in previous research.